Engineering biochar with multiwalled carbon nanotube for efficient phase change material encapsulation and thermal energy storage. (1st February 2021) - Atinafu, Dimberu G.; Wi, Seunghwan; Yun, Beom Yeol; Kim, Sumin
Abstract: Currently, numerous efforts are being made to develop shape-stabilized composite phase change materials (PCMs) to respond to unbalanced renewable energy storage systems. In this study, we engineered hybrid materials based on commercially available and environmentally friendly biochar derived from bamboo and multiwalled carbon nanotubes (CNTs) via a one-step hydrothermal method. The organic liquid n-dodecane was used as the energy storage material. The hybrid material provides favorable morphological and interconnected framework structures for PCM encapsulation and energy storage capacity in the composite PCMs. The PCM loading capacity of biochar, biochar-CNT, and CNTs reached 51.3%, 70.6%, and 83.2% with latent heat of 93.4 ± 1.1, 127.3 ± 1.1, and 152.3 ± 1.3 J/g, respectively. The integration of CNTs with biochar positively affected the latent heat storage capacity of the composite PCMs compared with that of the composite PCMs without CNTs. The pristine biochar exhibited a low PCM loading ratio and latent heat compared with biochar-CNTs and CNTs, presumably due to the limited pore space and strong intermolecular interaction between the reactive functional groups and PCM. Meanwhile, the obtained composite PCMs exhibited outstanding shape and thermal stabilities and chemical compatibilities. This synthesis strategy is expected to create a platform for fabricating biochar-based multifunctional PCMs for desired applications. Highlights: A biochar-integrated multiwalled carbon nanotube hybrid was designed and employed as n-dodecane support. The hybrid material provides a suitable microstructure for high phase change material (PCM) loading. PCM introduced into pristine biochar and biochar-CNT revealed a heating enthalpy of 127.3 J/g and 152.3 J/g, respectively. The composite PCMs displayed high chemical compatibility and shape/thermal stabilities.